The Relationship between Islamic Microfinancing, Energy Supply Adequacy and Performance of Agriculture Microenterprises - Ruslan Rafiatul Adlin Mohd; Rashid Intan Maizura Abd; Shafiai Syahiru; Fianto Bayu Arie; Yusof Azman Mohd. (ECONOMICS)
Empowering microenterprises has been shown to be effective in alleviating poverty and raising income. It is extremely effective in all nations when combined with the promotion of Islamic microfinance. Agriculture microenterprises focus on fisheries and aquaculture, agriculture trade, food, and other agriculture-related companies. Islamic microfinance plays a critical role in enhancing transaction circulation and agricultural community awareness of financial management because agricultural community income varies by season. From 2002 to 2022, this study looks into the factors that influence Islamic microfinance, energy supply sufficiency, and the performance of agriculture microenterprises in Malaysia. It uses a concurrent model of Islamic microfinance, energy supply adequacy, and a set of measures related to agriculture microenterprises sector performance that are deemed to be important in terms of supply chain linkages and raw material access. The data indicate that the goal of descriptive analysis is to clarify the generous condition for all variables involved in the study. Four analyses have been carried out. The first step is descriptive analysis. Then, the normality Test, and the third is the Correlation Analysis. Finally, the regression analysis will be used to estimate the relationship between the dependent and independent variables. Based on the simultaneous relationship, the study yields positive and negative results. The findings suggest that the performance of Malaysian agricultural microenterprises is more affected by Islamic microfinance, according to a causality analysis.